Girls-Boys: An Investigation of Gender Differences in the Behavioral and Neural Mechanisms of Trust and Reciprocity in Adolescence - Lemmers-Jansen, Imke L. J.; Fett, Anne-Kathrin J.; Shergill, Sukhi S.; van Kesteren, Marlieke T. R.; Krabbendam, Lydia (Frontiers in Human Neuroscience, 2019)
Background: Trust and reciprocity towards others have often been found to increase from childhood to adulthood. Gender differences in these social behaviors have been reported in adults. While adolescence is a key-period of change in social behavior, gender differences in trust and reciprocity during this developmental stage have rarely been investigated. Method: Here we investigate age-related gender differences in trust and reciprocity (n = 100, 51 female) and associated neural mechanisms (n = 44, 20 female) in adolescents between 13 and 19 years of age. Participants played two multi-round trust games with a pre-programmed cooperative and an unfair partner. Forty-four of 100 participants completed the trust game while undergoing functional brain imaging. Results: Participants’ investments were greater towards a cooperative than unfair game partner (p < 0.01), showing sensitivity to the degree of trustworthiness. There were no gender or age or related differences in baseline trust. In repeated cooperative interactions no gender differences were found, but younger adolescents showed slightly steeper increase of investments than older adolescents. In unfair interactions, younger males reacted with stronger decrease of investments than older males. Region of interest analysis of brain areas associated with in mentalizing, reward learning, conflict processing, and cognitive control revealed gender-by-age interactions on trusting behavior in the temporo-parietal junction (TPJ) and the caudate, showing stronger influence of age in males than in females during cooperation, and the reverse in unfair interactions. Additionally, main effects of gender were found in the TPJ, with higher activation in males, and in the caudate, with females showing greater activation. Conclusion: In first interactions and during repeated cooperative interactions, adolescent males and females showed similar trusting behavior. Younger males showed stronger responses to unfairness by others. Gender-by-age interactions in specific ROIs suggest differential development in mentalizing and reward related cognitive processes. In conjunction with previous research, our findings suggest the presence of subtle gender and age-related changes in trust and cooperation that are only detectable using larger age windows.